Firm performance, retrenchment strategy and different ownership structure: Evidence from public listed companies in Malaysia - Lik-Jing Ung; Rayenda Brahmana; Chin-Hong Puah (International Journal of Business Science & Applied Management (IJBSAM), 2018)
This research aims to investigate the relationship between retrenchment strategy and firm performance for a sample of 119 listed firms in Malaysia over the period 2008-2015. Using robust panel regression, we find that retrenchment strategy contributes positively to firm performance. Our research further indicates that controlling shareholders plays a significant role in the association between retrenchment strategy and firm performance, in which retrenchment strategy decreases the performance of family and government-linked firms. Our findings contribute to Malaysian firms, government, and policymakers by showing that retrenchment strategy may harm the performance of firm if the firms are family firms or government-linked firms.
Keywords: 650; retrenchment; controlling shareholder; firm performance; corporate governance